2017
DOI: 10.1016/j.ajpath.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Tight Junction Proteins Claudin-1 and Occludin Are Important for Cutaneous Wound Healing

Abstract: Tight junction (TJ) proteins are known to be involved in proliferation and differentiation. These processes are essential for normal skin wound healing. Here, we investigated the TJ proteins claudin-1 and occludin in ex vivo skin wound healing models and tissue samples of acute and chronic human wounds and observed major differences in localization/expression of these proteins, with chronic wounds often showing a loss of the proteins at the wound margins and/or in the regenerating epidermis. Knockdown experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 61 publications
6
49
0
Order By: Relevance
“…A recent study by Volksdorf et al showed that loss of claudin 1 and occludin occurs at the wound margins of chronic wounds and in the regenerating epidermis [16]. On the basis of these results, together with our microarray analyses, we hypothesized that inhibition of CLDN1 or OCLN expression could affect the migratory and proliferative capacity of skin and oral keratinocytes.…”
Section: Inhibition Of Claudin 1 or Occludin Alters Migration And Prosupporting
confidence: 60%
See 1 more Smart Citation
“…A recent study by Volksdorf et al showed that loss of claudin 1 and occludin occurs at the wound margins of chronic wounds and in the regenerating epidermis [16]. On the basis of these results, together with our microarray analyses, we hypothesized that inhibition of CLDN1 or OCLN expression could affect the migratory and proliferative capacity of skin and oral keratinocytes.…”
Section: Inhibition Of Claudin 1 or Occludin Alters Migration And Prosupporting
confidence: 60%
“…TJs also maintain cell polarity and prevent mixing of molecules from the apical and lateral membranes, a role termed fence function. In addition, some TJ genes also regulate the proliferation and migration of epithelial cells [15,16] and are involved in the immune response [17]. Given the differential healing phenotypes of cutaneous skin and oral wounds and the critical roles that TJs play in various tissues, we hypothesized that the repertoire of expressed TJ genes may be different between the skin and oral cavity in both intact epithelial cells and in a wound healing setting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they influence SC formation and function . Furthermore, TJ proteins have been shown to be involved in keratinocyte proliferation, differentiation, migration, apoptosis and cell‐cell adhesion . Thus, TJs and distinct TJ proteins are interesting to address for investigation of epidermal barrier function, epidermal differentiation, epidermal ion gradients and wound healing.…”
Section: D Skin Models To Study the Physical Skin Barrier: From Stramentioning
confidence: 99%
“…Thus, we analyzed the expression level of Claudin1, Occludin, and ZO‐1 in HaCaT human keratinocytes treated with the ethanol extract of L. cuneata G. Don by Western blotting. As shown in Figure a, Claudin1, Occludin, and ZO‐1 was up‐regulated by the ethanol extract of L. cuneata G. Don in HaCaT cells, which was confirmed by wound healing migration assay as the enhanced TJ function can affect cell mobility and migration (Volksdorf et al., ) (Figure b). The treatment of 250 and 500 μg/ml of the ethanol extract of L. cuneata G. Don has significantly increased the expression of Claudin1, Occludin, and ZO‐1 compared to the vehicle control.…”
Section: Resultsmentioning
confidence: 70%
“…Among these proteins, claudins have several types of isomers that are mainly responsible for TJ depending on the tissue types (Shigetomi & Ikenouchi, 2017). Especially, in skin keratinocytes, claudin-1 is known to be involved in regulation of TJ and its functional mechanism has been studied by several recent reports (Tokumasu, Tamura, & Tsukita, 2017;Tokumasu et al, 2016;Volksdorf et al, 2017). As TJ plays a significant role in skin barrier function, researcher have been considering the novel way for preventing and strengthening skin barrier by the development of various cosmetic materials to control TJ in skin.…”
mentioning
confidence: 99%